THE USE OF ALUMINIUM SOLID WASTE AS AN ALTERNATIVE MATERIAL FOR CASTING IN SCULPTURE: THE CASE OF NKAWIE SENIOR HIGH TECHNICAL SCHOOL, GHANA - Addai, Emmanuel; Kwabena Agyei, Isaac; Ama Fening, Peggy; Adu-Agyem, Joe; Ofori Addo-Danquah, Sam (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
Casting is important for the mass production of designs and therefore plays a critical role in sculpture and other forms of art. Nevertheless, the application of many new and innovative machineries and conventional materials during practical sessions in the teaching and learning of metal casting raises the cost load on students coupled with some unfriendly orthodox materials which contain harmful compounds and are detrimental to human health. The purpose of this study is to explore solid waste aluminium for metal casting in sculpture. Non-biodegradable materials with aluminium in them were collected from restaurants and pubs, gutters, landfills, funeral and party grounds, and aluminium window and frame producers in the Atwima Nwabiagya Municipality in Nkawie district. Solid waste aluminium identified were sorted, shredded, and washed to make it ready for melting and poured into a mother mould for final casting. Beverage cans with brand names such as Malt, Coca-Cola, Sprite, Adonko Next Level, Milo, and others, including waste aluminium chips, waste aluminium window frames and doors, and waste aluminium from fufu pounding machines, are part of the significant ones recognised to produce a sizable amount of molten metal for casting. This study made use of quantitative-quasi-experiment, case study and action research methods. Focus group interviews, personal observation of the solid waste aluminium materials were employed for metal casting. These materials were recycled and used by art students and teachers for teaching and learning sculpture as well as their project work. In each stage of the study, experiential learning was found to be the most effective method of problem-solving. Based on the evidence gathered in this study, the most valuable outcomes are group learning through association and cooperative problem-solving. This study has demonstrated that when students actively engage in this learning process, they learn more effectively. Plaster mould casting has been shown to be feasible in the classroom without the need for lost wax method of casting. There is no need to manufacture vents or gating systems. Identifying alternative materials by teachers and students at all levels of sculpture learning must be prioritized. With the continuing divergence in aesthetic responsiveness, creativity, and sustainable development, sculpture teachers and sculptors must turn to solid-waste aluminium as an alternative medium for teaching, learning, and producing artwork.